Strategies of nonconventional Market segmentation: the consequences of the use of local language in a hypermarket - SILLANI, SANDRO; ROSA, FRANCO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
This work sprang from the interest that various firms have in market segmentation according to local language and proposes a definition of linguistic segmentation of the market and linguistic segment. Empirical evidence was collected by testing the use of Friulian in a hypermarket. It emerged that: 1) the lack of linguistic segmentation among customers determined a non-detectable impact of the indications reported in local language; 2) changing the format of communication can facilitate customer satisfaction.